1990
DOI: 10.1177/026988119000400105
|View full text |Cite
|
Sign up to set email alerts
|

The differential effects of flumazenil on the psychomotor and amnesic actions of midazolam

Abstract: Forty-four patients given midazolam prior to day-care urological surgery had the benzodiazepine antagonist, flumazenil, or placebo administered postoperatively. Flumazenil reversed the psychomotor impairments induced by midazolam but not its amnesic effects. There was no evidence of resedation for up to 6 h following the use of flumazenil.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

1991
1991
2005
2005

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(8 citation statements)
references
References 15 publications
1
7
0
Order By: Relevance
“…β-CCt failed to block the amnesic actions of chlordiazepoxide in the passive avoidance test and the radial arm maze in mice (Belzung et al 2000). Similarly, several human studies found that flumazenil blocked the sedative and psychomotor effects of benzodiazepines, but not their amnesic effects (Birch and Curran 1990;Curran and Birch 1991;Hommer et al 1993;Birch and Miller 1995), while in others (Dorow et al, 1987;Ghoneim et al 1989;Preston et al 1989;McKay et al 1990), the effective reversal of amnesic effects of benzodiazepines was obtained. Hence, Curran (1991) concluded that, in humans, the sedative effects of benzodiazepines are much more easily reversed than their amnesic effects.…”
Section: Discussionmentioning
confidence: 95%
“…β-CCt failed to block the amnesic actions of chlordiazepoxide in the passive avoidance test and the radial arm maze in mice (Belzung et al 2000). Similarly, several human studies found that flumazenil blocked the sedative and psychomotor effects of benzodiazepines, but not their amnesic effects (Birch and Curran 1990;Curran and Birch 1991;Hommer et al 1993;Birch and Miller 1995), while in others (Dorow et al, 1987;Ghoneim et al 1989;Preston et al 1989;McKay et al 1990), the effective reversal of amnesic effects of benzodiazepines was obtained. Hence, Curran (1991) concluded that, in humans, the sedative effects of benzodiazepines are much more easily reversed than their amnesic effects.…”
Section: Discussionmentioning
confidence: 95%
“…Such a result would provide evidence that implicit and explicit memory are mediated by different memorial factors. 1 Studies using the benzodiazepine antagonist flumazenil have shown evidence inconsistent with the hypothesis that midazolam amnesia is due to a state-dependent memory effect in free recall (Birch & Curran, 1990;File, Goodall, Mabbutt, Harris, & Skelly, 1993). Specifically, such studies show that although flumazenil reverses midazolam's major sedative effects (e.g., psychomotor performance returns to normal levels), midazolam's amnesic effects remain, and are as strong as in a condition where participants are administered an injection of saline prior to free recall.…”
Section: Characteristics Of Midazolam Amnesiamentioning
confidence: 99%
“…This selective pattern of cognitive dysfunction may serve as a model for clinical cognitive syndromes. [ 112,216,217] A variation of the hypoxia model is that of hyperventilation-induced cognitive dysfunction. This model has previously been shown to be more valid for the simulation of ischaemic events in the brain than the hypoxia model and also that it is a sensitive model to test the neuroprotective effects of nootropic drugs such as aniracetam.l 60 ] Recently, hyperventilation-induced cognitive dysfunction was demonstrated employing a variety of cognitive tests.…”
Section: Future Possibilitiesmentioning
confidence: 99%